Preliminary Experience Using Full-Spectrum Endoscopy for Colorectal Cancer Screening: Matched Case Controlled Study - Sayo Ito; Kinichi Hotta; Kenichiro Imai; Masao Yoshida; Kimihiro Igarashi; Yuichiro Yamaguchi; Kohei Takizawa; Naomi Kakushima; Masaki Tanaka; Noboru Kawata; Hiroyuki Matsubayashi; Hirotoshi Ishiwatari; et al. (Gastroenterology Research and Practice, 2016)
Background/Aim. High-quality colonoscopy is needed to reduce the morbidity and mortality of colorectal cancer. Full-spectrum endoscopy (FUSE) has recently shown potential in improving adenoma detection during colonoscopy. This study aimed to evaluate the feasibility and utility of FUSE colonoscopy. Methods. From April 2015 to February 2016, 130 patients underwent FUSE colonoscopy for screening at a tertiary cancer center. Cecal intubation rate (CIR), procedure time, polyp/adenoma detection rate (PDR/ADR), and mean number of adenomas per colonoscopy (APC) were compared in matched-control patients (n=260) who underwent standard colonoscopy (SC). Accordingly, endoscopists subjectively evaluated the utility of FUSE colonoscopy. Results. The CIR of FUSE colonoscopy was 94.6%. Cecal intubation time (8.8 min versus 5.1 min, P<0.001) and total procedure time (21.6 min versus 17.3 min, P<0.001) in the FUSE group were significantly longer than those in the SC group. PDR (68.3 versus 71.2%, P=0.567), ADR (63.4% versus 58.5%, P=0.355), and APC (1.4 versus 1.4, P=0.917) were not significantly different between the two groups. The wide view of FUSE colonoscopy was superior to that of SC based on the questionnaires. Conclusions. FUSE colonoscopy did not demonstrate superiority to SC in a clinical setting.